2007
DOI: 10.1177/112067210701700612
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Complement Factor H Y402H Polymorphism on the Outcome of Photodynamic Therapy in Age-related Macular Degeneration

Abstract: The dysfunction of the CFH related to the risk of AMD and caused by the Y402H polymorphism does not modify the outcome of PDT. Genotyping for CFH Y402H cannot be used to select patients for this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 29 publications
(24 reference statements)
1
29
2
Order By: Relevance
“…Previous reports evaluated only CFH Y402H as a predictor for the outcome of PDT in neovascular AMD [10][11][12][13][14]. However, our results suggested that the association for the response to PDT was not only with Y402H, but also with rs1410996 in the CFH region.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Previous reports evaluated only CFH Y402H as a predictor for the outcome of PDT in neovascular AMD [10][11][12][13][14]. However, our results suggested that the association for the response to PDT was not only with Y402H, but also with rs1410996 in the CFH region.…”
Section: Discussioncontrasting
confidence: 56%
“…Although the conclusions of previous reports regarding the association of CFH with the effects of PDT in neovascular AMD were contradictory [10][11][12][13][14], we found that coding variants in CFH were significantly associated with the response to PDT in PCV. This may be explained by differences in the phenotype (neovascular AMD vs PCV) or differences in the method of subgroup classification.…”
Section: Discussioncontrasting
confidence: 31%
See 2 more Smart Citations
“…(62) Other studies did not show significant association between CFH polymorphism and PDT response for neovascular AMD. (63,64) For LOC387715, two important studies have shown that there is no statistical significant difference among the genotypes in response to PDT. (62,65) However, Sakurada et al have recently shown that there is a pharmacogenetic association between the LOC387715 A69S variant and the long-term results after PDT in eyes with polypoidal choroidal vasculopathy (PCV).…”
Section: Introductionmentioning
confidence: 99%